The reality of professional development for public school teachers in Lebanon and its obstacles from the perspective of a sample of principals: Teacher training in the Beirut Governorate as a model - Mhanna, Ali Habib (Journal of Educational and Psychological Sciences, 2025)
This research aimed to identify the reality of professional development for teachers in public schools in Lebanon, from the point of view of principals and teacher trainers. The research adopted a mixed method (quantitative and qualitative) approach, where the study was applied to a sample of 15 public schools in the Beirut governorate. The researcher used two used two tools to collect data, the first is a questionnaire addressed to principals and the second is an interview with the head of the preparation and training office at the Educational Center for Research and Development. The research results indicated that the responses of the study sample across all dimensions of the questionnaire were (I somewhat agree), as the overall arithmetic means of the study sample’s responses ranging between 1.62 and 1.98. This indicates that the principals did not adopt a decisively positive stance regarding the impact of professional development on teachers’ performance in public schools, in addition to the existence of many gaps in the development process, most notably the lack of coordination between those responsible for development, the lack of scientific evaluation of training, and the lack of follow-up for teachers after they receive training. Based on the results, the researcher recommended the necessity of professionalizing the training apparatus and linking the teacher’s performance to their career advancement. He also established the necessary mechanisms for coordination among all relevant parties and providing sustainable professional development programs that address the actual needs of teachers to improve their performance, as well as granting school principals the authority to develop their teachers according to their specific needs.